Hak Warga Negara dalam Menyampaikan Kebebasan Berpendapat Berdasarkan Peraturan Perundang-Undangan Perspektif Fiqh Siyasah - Adliano Dino Dachi; Khalid Khalid (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Freedom of speech is one of the most important human rights. Freedom of opinion requires individuals to express opinions and opinions without fear of retaliation or punishment from the government or other entities. The important role of freedom of opinion is closely related to human rights in ensuring an open and democratic political system and can help in fighting for other human rights. In this research, it will examine more deeply about freedom of opinion based on laws and regulations that aim to achieve the right of freedom in expressing opinions on something reviewed from Law Number 9 of 1998 concerning Freedom to Express Opinions in Public with the perspective of Fiqh Siyasah and Maqashid Syari'ah. Keywords: Opinion, Human Rights, Fiqh Siyasah